Google analytics breakthrough : from zero to business impact - Alhlou, Feras (Hoboken, New Jersey : John Wiley & Sons, Inc, 2016)
A complete, start-to-finish guide to Google Analytics instrumentation and reporting Google Analytics Breakthrough is a much-needed comprehensive resource for the world's most widely adopted analytics tool. Designed to provide a complete, best-practices foundation in measurement strategy, implementation, reporting, and optimization, this book systematically demystifies the broad range of Google Analytics features and configurations. Throughout the end-to-end learning experience, you'll sharpen your core competencies, discover hidden functionality, learn to avoid common pitfalls, and develop next-generation tracking and analysis strategies so you can understand what is helping or hindering your digital performance and begin driving more success. Google Analytics Breakthrough offers practical instruction and expert perspectives on the full range of implementation and reporting skills: -Learn how to campaign-tag inbound links to uncover the email, social, PPC, and banner/remarketing traffic hiding as other traffic sources and to confidently measure the ROI of each marketing channel -Add event tracking to capture the many important user interactions that Google Analytics does not record by default, such as video plays, PDF downloads, scrolling, and AJAX updates -Master Google Tag Manager for greater flexibility and process control in implementation -Set up goals and Enhanced Ecommerce tracking to measure performance against organizational KPIs and configure conversion funnels to isolate drop-off -Create audience segments that map to your audience constituencies, amplify trends, and help identify optimization opportunities -Populate custom dimensions that reflect your organization, your content, and your visitors so Google Analytics can speak your language -Gain a more complete view of customer behavior with mobile app and cross-device tracking -Incorporate related tools and techniques: third-party data visualization, CRM integration for long-term value and lead qualification, marketing automation, phone conversion tracking, usability, and A/B testing -Improve data storytelling and foster analytics adoption in the enterprise Millions of organizations have installed Google Analytics, including an estimated 67 percent of Fortune 500 companies, but deficiencies plague most implementations, and inadequate reporting practices continue to hinder meaningful analysis. By following the strategies and techniques in Google Analytics Breakthrough, you can address the gaps in your own still set, transcend the common limitations, and begin using Google Analytics for real competitive advantage. Critical contributions from industry luminaries such as Brian Clifton, Tim Ash, Bryan and Jeffrey Eisenberg, and Jim Sterne - and a foreword by Avinash Kaushik - enhance the learning experience and empower you to drive consistent, real-world improvement through analytics.
Introduction -- Google analytics reporting overview : user characteristics and behavior -- Measurement strategy -- Account creation and tracking code installation -- Google tag manager concepts -- Events, virtual pageviews, social actions, and errors -- Acquisition reports -- Goal and ecommerce tracking -- View settings, view filters, and access rights -- Segments -- Dashboards, custom reports and intelligence alerts -- Implementation customizations -- Mobile app measurement -- Google analytics integrations : the power of together -- Integrating Google analytics with CRM data -- Advanced reporting and visualization with third-party tools -- Data import and measurement protocol -- Analytics 360.
Includes index.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Business; Marketing; Strategy -- Data processing; Marketing; Affaires; Marketing; marketing; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Reference; BUSINESS & ECONOMICS -- Skills; Business; Marketing; Strategy -- Data processing